2019
DOI: 10.1016/j.bbi.2019.01.016
|View full text |Cite
|
Sign up to set email alerts
|

Understanding associations of early-life adversities with mid-life inflammatory profiles: Evidence from the UK and USA

Abstract: Objectives: In two cohorts, we aimed to establish associations between early-life adversities and adult inflammation, and whether adult (a) adiposity or (b) socioeconomic disadvantage are key intermediaries. Methods: In both cohorts (N=7,661, 1958 British birth cohort; N=1,255, MIDUS), information was used on adult inflammatory markers (C-reactive protein (CRP), fibrinogen and (MIDUS only) interleukin-6 (IL-6)), adiposity and socioeconomic disadvantage, and early-life adversities (neglect, emotional neglect, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
33
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 48 publications
0
33
0
Order By: Relevance
“…This is consistent with theoretical work by McLaughlin et al (2014) which suggests that threat-based adversities are more likely to activate the HPA axis and consequently result in chronic inflammation. Previous work on the 1958 cohort also showed higher inflammation for those reporting physical abuse (Pinto Pereira et al, 2019). In contrast, a recent study showed that official reports, but not retrospective self-reports, of physical abuse were associated with higher CRP (Osborn and Widom, 2019).…”
Section: Interpretation Of Study Findingsmentioning
confidence: 79%
“…This is consistent with theoretical work by McLaughlin et al (2014) which suggests that threat-based adversities are more likely to activate the HPA axis and consequently result in chronic inflammation. Previous work on the 1958 cohort also showed higher inflammation for those reporting physical abuse (Pinto Pereira et al, 2019). In contrast, a recent study showed that official reports, but not retrospective self-reports, of physical abuse were associated with higher CRP (Osborn and Widom, 2019).…”
Section: Interpretation Of Study Findingsmentioning
confidence: 79%
“…However, there is burgeoning evidence of an association between neglect in particular and elevated IL‐6 levels (Chase et al, 2019; Nikulina and Widom, 2014). Evidence for elevated CRP is mixed, with some studies reporting an association between neglect and greater CRP levels (Pinto Pereira et al, 2019), an association limited to certain racial groups (Nikulina and Widom, 2014), or no association (see Ports et al, 2019 for a review). It is notable that neglect (i.e., institutional deprivation) limited to infancy and early childhood is not associated with increased cytokines or CRP in circulation by adolescence or young adulthood (Elwenspoek et al, 2017; Slopen et al, 2019).…”
Section: Models Of Neglectmentioning
confidence: 99%
“…Both early life experiences and social environments during adulthood can have profound effects on individual health and survival. Children who experience socioenvironmental traumas—from famine to parental loss to abuse—fare worse on a wide range of health outcomes in adulthood ( 1 9 ). They are also disproportionately likely to find themselves in negative social environments as adults, including having dysfunctional or unsupportive relationships, or being socially isolated ( 10 12 ).…”
mentioning
confidence: 99%